UPAYA GURU PENDIDIKAN AGAMA ISLAM UNTUK MEMBINA AKHLAK MAHMUDAH SISWA DI SMP MUHAMMADIYAH SIMPANG EMPAT - Diana Diana (Tarbiya Islamica, 2013)
This research begins with seeing the problems that occur in schools, there are some studens who are not enough to have a commendable character, therefore the teacher tries to build morals. The data source of this research is the information obtained from the pie teacher, principal, junior high school students. The method used in this research is descriptive method with a qualitative approach. Data collection techniques and tools are interviews, observation and documentation. The data that has been collected is then processed using data analysis, namely data collection analysis, data presentation or data display and drawing conclusions or verification. The research results can be concluded : 1) the efforts of Islamic religious education teachers to foster easy morals for studens at SMP Muhammadiyah Simpang Empat Academic Years 2019/2020 that is : Islamic religious education teachers explain praiseworthy moral actions, Islamic religious education teachers take several approaches to students such as giving sanctions if students are not serious about receiving material, Islamic religious education teachers give rewards to students when students can answer questions. 2) the way Islamic religious education teachers to build student morals at SMP Muhammadiyah Simpang Empat Kecamatan Tangaran Academic Years 2019/2020 that is : Islamic religious education teachers use learning media when delivering praiseworthy moral materials, Islamic religious education teachers use methods in conveying praiseworthy material such as playing roles related to praiseworthy morals, Islamic religious education teachers always give commendable moral attiudes to students such as saying greetings, providing explantions for respecting elders such as respecting parents, not speaking harshly, Islamic religious education teachers provide explanations of the consequences if not accustomed to commendable morals.